Effects of Lactiplantibacillus plantarum WLPL01 fermentation on antioxidant activities, bioactive compounds, and flavor profile of Artemisia argyi. (October 2022) - Zhan, Hui; Xu, Wenfeng; Zhao, Xiangxiang; Tian, Linlin; Zhang, Fen; Wei, Hua; Tao, Xueying
Abstract: Artemisia argyi is a traditional Chinese food and medicine which can improve multiple diseases such as asthma and gastrointestinal disorders. However, whether the beneficial bioactivities are associated with microbial fermentation remain unknown. The objective of this study was to investigate the effects of fermentation on bioactive compounds, antioxidant activity, and flavor characteristics of Artemisia argyi fermentation liquid (AAFL-LP) by an autochthonous strain, Lactiplantibacillus plantarum WLPL01. L. plantarum WLPL01 was found to utilize sugars and flavonoids to produce abundant organic acids, such as lactic acid and malic acid, improve antioxidant activity of Artemisia argyi including total superoxide dismutase content, 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging capacity, and Fe-reducing antioxidant power, decrease largely bitter taste notes such as leucine, isoleucine, and phenylalanine, and enhance fruity, sweet, and flora notes such as terpenes and esters of AAFL-LP. Collectively, L. plantarum WLPL01 could improve the functionality of A. argyi and the flavor of the product, suggesting it a promising candidate in developing functional A. argyi food. Highlights: L. plantarum WLPL01 fermentation enhanced the antioxidant activity of A. argyi. L. plantarum WLPL01 fermentation increased the bioactive compounds of A. argyi. 70 volatile compounds were identified in A. argyi and its fermentation liquid.